(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The main objective to develop and develop logical thinking abilities, to express themselves independently, to expand students’ thinking worldviews, and to educate them of their minds and the virtue of preparation. The textbook of mathematics involves teaching students how to solve certain different issues by creating equations